2018
DOI: 10.1503/cmaj.180177
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in outcomes of heart failure in an ambulatory, population-based cohort from 2009 to 2013

Abstract: Despite decreases in overall heart failure incidence and mortality in ambulatory patients, mortality rates remain higher in women than in men, and rates of hospital admission for heart failure increased in women and declined in men. Further studies should focus on sex differences in health-seeking behaviour, medical therapy and response to therapy to provide guidance for personalized care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
29
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 35 publications
10
29
0
2
Order By: Relevance
“…Consistent with our higher percentage of women (57%) first admitted because of AHF, similar data have been published in Canada, where an increasing trend of rates of hospital admission were detected in women and declining in men . Furthermore, previous studies have shown that women presented more commonly with “de novo” AHF than men …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with our higher percentage of women (57%) first admitted because of AHF, similar data have been published in Canada, where an increasing trend of rates of hospital admission were detected in women and declining in men . Furthermore, previous studies have shown that women presented more commonly with “de novo” AHF than men …”
Section: Discussionsupporting
confidence: 91%
“…Similarly, as previously published, the present results were in accordance to other HF studies assessing differences between sex, in which women on their first admission for HF are usually older, with hypertensive rather than ischemic etiology . Unfortunately, as not all of our included patients had systematic echocardiographic study carried out on admission, we could not confirm the reported predominance of preserved HF in women . The higher percentage of dementia in older women with HF has been previously reported as well .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations